Analysisofmissensesnpsin Humanlrp5 Gene By In Silicoapproach (Applied Biological Research, 2023)
Low-density lipoprotein receptor-related protein 5 (LRP5) is a protein, encoded  by the LRP5 gene in humans. LRP5, the key component of the LRP5/LRP6/ Frizzled co-receptor group is involved in canonical Wnt pathway, a regulator of  bone metabolism. Mutations in LRP5 can lead to considerable changes in bone  mass following bone diseases. Our study aimed to predict the effect of missense  SNPs in human LRP5 gene by in silico methods using publicly available online  software tools and database. We predicted the functional effects of mutations by  using VEP, PROVEAN, SNPs & GO, and PANTHER, effects on the stability of  the protein by I-Mutant 2.0 and on the 3-Dstructure of the protein by Project  HOPE. We used GeneMANIA to predict the interaction of LRP5 with 20 other  genes. Over all this is a comprehensive study provides all the available  information about the clinically significant missense SNPs of LRP5 at a glance.
Keywords: Bone diseases; 3D structural effect; functional effect; in silico; LRP5; missense SNPs analysis